Investigating the value of spatiotemporal resolutions and feedback loops in water-energy nexus modeling. (November 2021) - Mounir, Adil; Guan, Xin; Mascaro, Giuseppe
Abstract: Modeling the interactions between water and energy is crucial to managing holistically these resources. Here, we simulate water allocations and energy dispatch in the metropolitan region of Phoenix, Arizona in 2008–2017 using the WEAP and LEAP models under different spatiotemporal resolutions and coupling configurations. We find that increasing the temporal resolution from annual to monthly allows capturing seasonal demands, which improves the simulation of water allocations from supply sources to all demand nodes; the simulation of energy fluxes is instead less sensitive to the model time step. Representing the domain with higher spatial granularity enhances the ability to model the correct water portfolio of the power plants. Finally, coupling the models to capture two-way feedbacks between water and energy systems improves the simulations of electricity generation and, in turn, of water fluxes. While related to Phoenix, our findings provide useful insights to improve water-energy nexus modeling at other sites. Highlights: Increasing time resolution is key to model water and energy demand seasonality. Modeling water supply dynamics is sensitive to the temporal resolution. Refining spatial granularity improves simulation of water supply sources. Coupled models improve simulation of electricity generation. Coupled models simulate larger intra-annual variability of water fluxes.